A comparative study of resilience in sexual minorities and cisgender individuals - Srishti Kapri; Sukhmani Singh (Discover Psychology)
Abstract Stress has become an inevitable aspect of daily life for almost everyone, although the causes of stress can vary from person to person. Being unable to identify with the gender assigned at birth can lead to significant stress. This study aims to investigate how being unable to identify with one’s assigned gender can impact an individual’s wellbeing. A comparison analysis was conducted between homosexual and heterosexual individuals to determine whose resilience is more at risk and the reasons behind it. The population in this study was chosen from City Chandigarh. The sample consists of 64 individuals who were given the Brief Resilience Scale (BRS), later on which was carefully analyzed. This study aims to present the perspectives of both minority group individuals and the cisgender population, which later on can be used to plan better mental health treatment plans and policies for the Minority Group. The results of this study shows that the difference in the level of resilience is almost negligible. Which helps us in understanding that resilience can be used as a preventive measure against mental health disparities faced by the LGBTQ + community.